Nutrient Intake, Feed Digestibility, and Growth Performance of Thin-Tailed Sheep Fed Complete Feed Containing Fermented Sargassum sp. - Dian Setya Budi; Andriyani Astuti; Ristianto Utomo (Buletin Peternakan, 2021)
The aim of this research was to identify the effect of feeding fermented Sargassum sp. as complete feed ingredient up to 20% of total feed on nutrient consumption and digestibility, and growth performance of thin-tailed sheep. Twelve female thin-tailed sheep aged 6 to 8 months with an average initial body weight of 14.13 ± 2.08 kg were divided into three groups. The treatments were control without fermented Sargassum sp. (S0), 10% fermented Sargassum sp. (S1), and 20% fermented Sargassum sp. (S2). Complete feed was formulated by isoprotein and isoenergy formulation, containing 16% of crude protein and 61% of total digestible nutrients. Complete feed was given at 3.5% of body weight (% dry matter) and drinking water was provided ad libitum. This research was done in 6 weeks with 14 days adaptation period and seven days of collection period. Growth performance was measured for 4 weeks after the adaptation period. The variables observed were dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), crude fiber (CF), nitrogen-free extract (NFE), and total digestible nutrients (TDN) consumption. The data obtained were subjected to one-way ANOVA (analysis of variance) and the difference existed (P value <0.05) between means were analyzed with Duncan’s multiple range test. The results showed that there was no significant effect of feeding fermented Sargassum sp. on nutrient intake, and digestibility of nutrients (P>0.05), however, S0 treatment appeared to have CP, CF, and EE intake, as well as digestibility of DM, CP, CF, and NFE higher than S1 and S2 treatment. The results showed that there was no significant effect of feeding fermented Sargassum sp. on nutrient intake, digested and digestibility of nutrient, absolute and relative weight gain as well as feed conversion.